PEMETAAN KARYA TULIS ILMIAH LPNK: STUDI KASUS LIPI DAN BPPT (2004-2008) - Royani, Yupi; A. Bachtar, Mulni; Tambunan, Kamariah; Tupan, Tupan; Sugiharto, Sugiharto (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2013)
This research aims to determine: the rank of authors of LIPI and BPPT whose articles are mostly cited by other authors, the type of publications, the level of collaboration, the productivity level of authors, the coverage areas, and the topics contained in the scientific work through the subject analysis. The data were obtained from Google Scholar from 2004 to 2008. The collected data were then analyzed by using ‘co-word’ analysis. The ‘co-word’ structure was known after the mapping using bibliometric method. A total of 593 analyzed scientific papers consist of 472 from LIPI and 121 from BPPT. The results show that the highest citation number (100 citations) comes from LIPI scientific papers, while BPPT scientific papers are 36 citations. Most types of publication produced by LIPI and BPPT are from journal articles and papers, each of 235 documents (49.79%) and 101 documents (21.40%) by LIPI and 71 documents (58.68%) and 42 documents (34.71%) by BPPT. LIPI researcher collaboration level was 0.82 and BPPT was 0.89. The most productive LIPI researcher in writing paper is Danny Hilman Natawidjaya (Geotechnology Research Center) with 31 scientific papers, while BPPT is Yusuf Surachman Djajadihardja with 34 scientific papers. The most dominant topic written by LIPI researcher is basic science or pure science i.e. 63.56%, with details: biology 131 documents (27.75%) followed by geology 121 documents (25.64%), chemistry 47 documents (9.96%) and mathematics 1 document (0.21%). The topic most widely written by BPPT researchers is the field of applied research i.e. 56.19% with the details: environment 33 (27.27%), engineering 27 (22.31%), biotechnology 5 (4.13%), food technology 2 (1.65%) and fisheries 1 document (0.83%). The relationship among the topics is shown in the line among the descriptors on each field. More relation lines among descriptors, the closer the relationships among documents.